Covariation of trophic and habitat‐related traits in chondrostoms (Cyprinidae): implications for repeated and diversifying evolutionary processes. (20th January 2015) - Corse, E.; Tarkan, A. S.; Emiroğlu, Ö.; Imsiridou, A.; Minos, G.; Lorenzoni, M.; Vilizzi, L.; Aboim, M. A.
Abstract: The tenet that ecological adaptation can lead to recurrent ecomorphological trends resulting from repetitive processes has long been a primary topic of investigation in evolutionary ecology. To explore this aspect further, this study provides an analysis of the morphological diversity in chondrostoms (Cyprinidae). This freshwater fish group shows a tendency towards bottom‐feeding specialization, which has led to evolutionary innovations in body and mouth shape traits, which are currently used for the classification of genera. Body, lower lip (LL) and corner ray shape were analysed for nine species in total. Allometric relationships among the three morphometric traits were considered to be responsible for LL shape variability and there was significant covariation between LL and body shape, which reflected habitat use. Smaller and opportunistic‐feeding species inhabiting stream or small‐sized rivers were characterized by a deeper body (increased feeding maneuverability), an arched LL and a terminal mouth position. Conversely, larger and diet‐specialized species were characterized by a fusiform body (increased swimming performance), a straight LL and an inframouth position on an elongated snout (optimized bottom feeding). The results suggest that interspecific mouth shape variability may have originated from two types of 'deformation' processes, both leading to a straight mouth shape and acting either jointly or independently. Also, given the plesiomorphic state of several of the species under study, the specialization towards a benthic lifestyle in chondrostoms from different phylogenetic lineages is thought to have occurred repeatedly to overcome a number of functional constraints, including foraging efficiency and swimming performance.